Formula recognizer a mathematical expression recognizer - Ate, Reena R. (2000)
When it comes to preparing documents on formulas, equations, and other expressions pertaining to mathematics, it is very difficult to represent symbols in true-type fonts. Without these special characters, the expression or formula is not correct and valid. Indeed, the best way to write them is to do them manually. This paper describes our research on the recognition of handwritten mathematical expressions. A tree structure based on the adjacency of pixels is used during segmentation to resolve the problem on overlapping bounding boxes. The use of additional features, like the width-height ration of the original image, is given as an additional input for recognition. Finally, the expression is generated using the original coordinates in the bitmap during parsing before it is converted to LaTeX format.